Analysis of the Archivistics Professional Association Organic Law project - Valverde Hernández, Fanny (2017)
The objective of this essay is to analyze some aspects of the Organic Law project of the Association of Archivists Professionals, through the study of the legislative file number 19389 in order to highlight several present disagreements. The omissions in the legislative process of consultations are exposed, characterization of the various professional’s archivists incorporated in another professional school, conflicts with the Law of the National System of Archives and other legislation. In addition, it is exposed the training of two organizations that present certain incongruities on this one: Costa Rican Association of Archivists (ACA, by its Spanish name) and the Interagency Commission of Heads of Public Sector Archives (CIAP, by its Spanish name); based on the number of members of both organizaciones and the administration and extinction of the second, the difficulty for the consolidation of an exclusive school is inferred. In addition, the Commission for the Creation of the Association of Archivists Professionals (CO-COLPROA, by its Spanish name) is considered, since it was the group that developed the project. In conclusion, three possible options are indicated: a) acceptance, b) requesting revision, or c) proposing a new replacement text.